OPTIMALISASI PEMBELAJARAN BERBASIS PROYEK DALAM MENINGKATKAN KESADARAN KEWARGANEGARAAN SISWA SESUAI PROFIL PELAJAR PANCASILA DI SMAN 1 SULIKI - Sonia; Buchari Nurdin; Azwar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study is motivated by the low level of civic awareness among students at SMAN 1 Suliki and the continued use of conventional teaching methods that do not actively involve students. This situation poses a challenge in realizing the Pancasila Student Profile, which emphasizes values such as collaboration, critical thinking, and social responsibility. The research aims to optimize project-based learning as a contextual and participatory approach to civic education. This qualitative research employed a descriptive method through observation, in-depth interviews, and documentation involving Civics teachers and Grade X students. Data were analyzed using the interactive model by Miles and Huberman, consisting of data reduction, data display, and conclusion drawing. The results revealed that: (1) project-based learning was systematically designed by integrating values of the Pancasila Student Profile, including collaboration, independence, and critical reasoning; (2) its implementation showed fairly good results, marked by active student participation in school-based social campaigns, although some aspects were not yet optimal due to limited teacher readiness and students’ need for more guidance; (3) supporting factors included school and teacher support, available learning media, and student collaboration, while inhibiting factors involved limited teacher training, time constraints, and lack of student experience in independent and group work. In conclusion, project-based learning contributed significantly to improving students’ civic awareness, though continuous improvement is needed in teacher training, time management, and student mentoring to ensure more effective and comprehensive implementation.